2015
DOI: 10.14737/journal.aavs/2016/4.1.46.52
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Dermoids in Crossbred Indian Cattle: A Comparative Evaluation of Four Year (2012 - 2015) Study Results and Literature Reviews

Abstract: | An exclusive literature on ocular dermoids in crossbred Indian cattle is currently unavailable except for sporadic reports. Medical records of past four years (2012)(2013)(2014)(2015) were investigated for evaluation of ocular dermoids in crossbred Indian cattle. The overall incidence of ocular dermoids was found to be 0.345% (5/1451). All the animals were less than five months of age. Based on anatomical location, four types of ocular dermoid were noticed either alone or in combination, both unilaterally an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These tissues or hair follicles usually irritate the eye and the animal suffers from chronic epiphora, conjunctivitis or keratitis and may even cause visual impairment (Nuh et al, 2012). Ocular dermoids in cattle have a low estimated prevalence of 0.002 % -0.4 % (Sarangom et al, 2016). It has been reported in cattle of many breeds worldwide, with a similar Plate III: The calf in lateral recumbency with temporary tasorrhaphy post dermoid excision surgery low prevalence in all breeds.…”
Section: Dermoid Occurs Sporadically In Numerous Cattlementioning
confidence: 91%
See 1 more Smart Citation
“…These tissues or hair follicles usually irritate the eye and the animal suffers from chronic epiphora, conjunctivitis or keratitis and may even cause visual impairment (Nuh et al, 2012). Ocular dermoids in cattle have a low estimated prevalence of 0.002 % -0.4 % (Sarangom et al, 2016). It has been reported in cattle of many breeds worldwide, with a similar Plate III: The calf in lateral recumbency with temporary tasorrhaphy post dermoid excision surgery low prevalence in all breeds.…”
Section: Dermoid Occurs Sporadically In Numerous Cattlementioning
confidence: 91%
“…Being a congenital anomaly, dermoid has been recorded in different cattle breeds and is believed to be non-heritable. The condition has been evaluated and reported exclusively in native Korean, Hereford, Israeli-Holstein and Nigerian cattle with an estimated prevalence of 0.35% (Ebbo et al, 2003;Bukar et al, 2008;Roh et al, 2014;Sarangom et al, 2016). In Nigeria, Ebbo et al (2003) and Akpavie et al (2006) reported bilateral corneal dermoid in a calf in Sokoto state, Nigeria while Bukar et al (2008) reported a 0.32% prevalence in Borno state, Nigeria.…”
Section: Introductionmentioning
confidence: 99%